2018
DOI: 10.1016/j.physletb.2018.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of gravitational-wave standard siren observation of the Einstein Telescope on weighing neutrinos in cosmology

Abstract: We investigate the impacts of the gravitational-wave (GW) standard siren observation of the Einstein Telescope (ET) on constraining the total neutrino mass. We simulate 1000 GW events that would be observed by the ET in its 10-year observation by taking the standard ΛCDM cosmology as a fiducial model. We combine the simulated GW data with other cosmological observations including cosmic microwave background (CMB), baryon acoustic oscillations (BAO), and type Ia supernovae (SN). We consider three mass hierarchy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 43 publications
1
77
0
Order By: Relevance
“…However, since the GW standard sirens can break the degeneracy, the combination of CMB+BAO+SN+GW finally can give a 2% w measurement in the wCDM model. Actually, Wang et al [62] further showed that the future GW standard sirens observed by the ET can also improve the constraints on the neutrino mass by about 10%. For other relevant investigations, see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the GW standard sirens can break the degeneracy, the combination of CMB+BAO+SN+GW finally can give a 2% w measurement in the wCDM model. Actually, Wang et al [62] further showed that the future GW standard sirens observed by the ET can also improve the constraints on the neutrino mass by about 10%. For other relevant investigations, see, e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In this section we shall describe the method for simulating the Gravitational Waves Standard Sirens (GWSS) data, each data point of which consists of (z, d L (z), σ d L ) of a GW source, where d L (z) is the luminosity distance at the redshift z and σ d L is the associated error with d L (z). The constraining ability of this catalogue, together with other astronomical datasets, is further investigated in various cosmological models, for instance [56,57,60]. The simulation of GW data is model dependent, thus one needs to choose the fiducial values of model parameters.…”
Section: Methods Of Simulating Gw Data and Its Usementioning
confidence: 99%
“…Following some earlier works in this direction [56,57,60], the redshift distribution of the observable sources is given by…”
Section: Methods Of Simulating Gw Data and Its Usementioning
confidence: 99%
See 2 more Smart Citations